A Study of Cheiloscopic Pattern in Relation to Gender and Blood Groups in a Tertiary Care Hospital at Chennai - S Surya; P Shruthi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Personal identification is of vital importance in forensic odontology for ethical, humanitarian and criminalenquiries. The applicability of Cheiloscopy ( study of pattern of lip print), one of the easiest tools availablein individual and medicolegal identification, is an area of extensive research in recent years. With theobjective to investigate the uniqueness of lip patterns in relation to gender and blood groups, this study wasconducted on 100 subjects, which included 50 males and 50 females. The lip prints obtained were studiedby applying Suzuki and Tsuchihashi’s classification.Type 2 (37%) was the most common lip print type inmales and Type 3 (38.5%) was the most common lip print type in females. The Lower lip print can helpin gender determination. No significant statistical correlation was found between the lip print patterns andblood group. Along with the traditional methods of identification like fingerprint analysis,Cheiloscopy canalso be helpful in the identification of a person.However, the utility of the same in forensic medicine stillremains largely untapped and unacknowledged. Similar studies with larger sample sizes are required toobtain statistically significant reports thereby allowing a more impactful emergence of lip print patternsusage in forensic analysis.